(untitled) (Revista de Biología Marina y Oceanografía, 2018)
Percnon pascuensis is redescribed based on adult specimens collected in Easter Island (today Rapa-Nui). The gonopod (first two pair of pleopod of males) structure is described by first time and compare with the other species of the genus. The analysis conclude that P. pascuensis is closely to P. sinensis based on the gonopods morphology. P. sinensis is distributed to China Sea. Earlier papers claim that P. pascuensis is closely related with P. planissimum, a widely distributed species, but both species are different morphology of the gonopods. P. pascuensis is a valid species seemingly endemic of the Easter Island.